Study on the clogging mechanism of upward inclined drainage holes in cut slopes - Meng, Jian; Chen, An; Yin, Kexin; Zhou, Caihui (Frontiers in Earth Science, 2023)
Since groundwater is one of the main factors affecting the stability of highway slopes in mountainous regions, its smooth drainage is essential for slope safety. After years of service, highway cut slopes often have drainage problems or even drainage failures that threaten their stability and safety. In this study, the mechanism of drainage hole clogging in highway cut slopes is firstly clarified through on-site surveys. Soil and blockage samples are collected from typical slopes for laboratory tests and analysis, revealing that all the blockages are made of fine-grained particles from the soils within the slopes. Scanning electron microscope (SEM) images reveal that the blockages penetrate the drainage pipe wrappings. The combined actions of clayey soil, chemicals, and biological clogging exacerbate the clogging process around drainage pipes. Laboratory tests are also performed to simulate the CaCO3 crystal clogging around the drainage holes, and the microstructure of the clogged geotechnical screens and geotextiles is observed using SEM. The results confirm that the amount of CaCO3 crystal attached to the drainage pipe surface increases with time. The single-layer structure of screens does not facilitate three-dimensional clogging like in the geotextiles. After soaking in diluted hydrochloric acid at the pH of 5.0, the screens and geotextiles show no significant decrease in the attached CaCO3 crystals. However, the decrease is apparent after soaking in hydrochloric acid at the pH of 3.0.